Effect of Ceramic Boron Carbide Particles Addition on the Mechanical and Microstructural Characteristics of Al7020 Alloy Composites - Shrishail Basappa Angadi; Santosh Kumar; Madeva Nagaral; Virupaxi Auradi; Balaraj Valukula (Mechanics of Advanced Composite Structures)
The aerospace and automotive engineering industries are seeing a growing need for materials that are both lightweight and very durable. This increased demand has prompted the development of innovative metal matrix composites based on aluminum. The current study aimed at developing and characterization Al7020 metal matrix composites by reinforcing micro boron carbide particles, Al7020/B4C MMCs are fabricated by stir casting method by varying the boron carbide particles in wt.% (0, 2, 4, 6, and 8wt. %). Lastly, the prepared samples were subjected to tensile, compression, hardness, and fracture toughness tests to evaluate the impact of B4C particles on density, mechanical, and microstructural parameters. By incorporating B4C particles into the Al7020 alloy, the experimental results demonstrated that metal matrix composites exhibited enhanced ultimate tensile strength, yield strength, hardness, and compression strength. In addition, the lowest density, highest toughness, and superior micrograph were observed in Al7020/B4C MMCs with 8 wt. % reinforcement of B4C particles with a minor decrease in elongation.